Thermodynamic and experimental explorations of CO2 methanation over highly active metal-free fibrous silica-beta zeolite (FS@SiO2-BEA) of innovative morphology - Hussain, I.; A. A., Jalil; S. M., Izan; M. S., Azami; K., Kidam; Nurul Aini, Razali; A., Ripin (Elsevier, 2021)
CO2 methanation is a novel way for climate change mitigation by converting CO2 into substitute natural gas. In this study, a highly active fibrous silica-beta zeolite (FS@SiO2-BEA) catalyst was prepared for CO2 methanation by a microemulsion process, and examined by N2 adsorption–desorption, field emission scanning electron microscope (FESEM), transmission electron microscopy (TEM), and electron spin resonance (ESR) spectroscopy techniques. It was found that the FS@SiO2-BEA catalyst possessed a fibrous silica morphology, leading to high surface area (609 m2/g), oxygen vacancies, and basicity. A thermodynamic study was also carried out using Gibbs free energy minimization method, and it was found that low temperatures (25–350 °C) and high H2: CO2 ≥ 4 ratios have enhanced the CO2 methanation activity. The prepared FS@SiO2-BEA catalyst exhibited high CO2 conversion (65%), and CH4 selectivity (61%) with a space–time yield of 3.30 g gcat−1 h−1. The obtained experimental results highly followed the thermodynamic calculations.